Kinetics Study of Ultrasound-assisted Hydrodistillation on Lemongrass (Cymbopogon citratus) leaves Essential Oil Production - Nurmawati, Ardika; Novita Indahyani; Luky Natasha; Pujiastuti, Yunita Ali (Journal of Biobased Chemicals, 2026)
Mechanisms in the essential oil production process continue to develop. Ultrasonic-assisted hydrodistillation (UAHD) is a highly efficient technique for essential oil production that reduces extraction time and increases essential oil yield through cavitation. However, kinetic modeling is required to understand the mass-transfer mechanism and facilitate process scaling. This study aimed to evaluate the extraction kinetics of essential oil from lemongrass (Cymbopogon citratus) leaves using the UAHD method and to identify the most suitable kinetic models among pseudo-first-order (PFO) and pseudo-second-order (PSO) equations in both linear and nonlinear forms. Experimental yield data were collected from the UAHD process, in which the ultrasonic procedure was performed at 40 °C for 10 minutes, followed by hydrodistillation at 100 °C for 30–150 minutes. The yield data were fitted into four kinetic models and assessed using statistical error analysis. The extraction process exhibited a two-phase profile (rapid initial washing and a slow diffusion phase). All models provided a reasonable fit, while the non-linear PSO model demonstrated the highest accuracy and the lowest error values. The non-linear PSO model predicted the equilibrium yield (qt) to be 14.0224 g, and the rate constant (k2) was 0.0049 kg g-1 min-1.